Advances in Neuroimaging and Monitoring to Defend Cerebral Perfusion in Noncardiac Surgery. (10th May 2022) - Fanning, Jonathon P.; Huth, Samuel F.; Robba, Chiara; Grieve, Stuart M.; Highton, David
Abstract : Noncardiac surgery conveys a substantial risk of secondary organ dysfunction and injury. Neurocognitive dysfunction and covert stroke are emerging as major forms of perioperative organ dysfunction, but a better understanding of perioperative neurobiology is required to identify effective treatment strategies. The likelihood and severity of perioperative brain injury may be increased by intraoperative hemodynamic dysfunction, tissue hypoperfusion, and a failure to recognize complications early in their development. Advances in neuroimaging and monitoring techniques, including optical, sonographic, and magnetic resonance, have progressed beyond structural imaging and now enable noninvasive assessment of cerebral perfusion, vascular reserve, metabolism, and neurologic function at the bedside. Translation of these imaging methods into the perioperative setting has highlighted several potential avenues to optimize tissue perfusion and deliver neuroprotection. This review introduces the methods, metrics, and evidence underlying emerging optical and magnetic resonance neuroimaging methods and discusses their potential experimental and clinical utility in the setting of noncardiac surgery. Abstract : The authors present an introduction to the emerging roles of neuromonitoring in optimizing perioperative care through guiding intraoperative hemodynamic management, improving surgical risk stratification, and enhancing diagnosis of postoperative neurologic sequelae.